Desirable personality traits of university lecturers from the technical students' perspectives - Salleh, R. (2013)
Lecturers' personality traits are integral in the overall picture of an excellent university lecturer. This study focused on understanding the personality traits of university lecturers that are desirable by final year engineering and technology students in Malaysia and explored the extent to which their perceptions differed according to gender and field of studies (engineering vs. technology). A total of 111 engineering and technology students participated in the study. The results revealed that helpful, approachable, fair and impartial, inspiring, concern for students and enthusiasm for subject as top rated traits of university lecturers. Interestingly, no significant difference was found between views of students from different gender and field of studies. Implications of the findings are discussed and recommendations for future research are put forward. Copyright Â© 2013 Salleh, R; Idrus, H. and Harun, H.